2017
DOI: 10.1039/c6cc09997a
|View full text |Cite
|
Sign up to set email alerts
|

moxDendra2: an inert photoswitchable protein for oxidizing environments

Abstract: Fluorescent proteins (FPs) that can be optically highlighted, enable PALM super-resolution microscopy and pulse-chase experiments of cellular molecules. Most FPs were evolved in and for the cytoplasm and, therefore, may fold incorrectly in subcellular organelles. Here, we describe the first monomeric photoswitchable from green to red bright FP adapted for oxidizing environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 21 publications
(28 reference statements)
0
19
0
Order By: Relevance
“…It was not obvious a priori that the cysteines of mMaple3 could be mutated without disrupting the desirable properties of mMaple3. Similar efforts for EGFP family members often resulted in dark proteins and our previous efforts with the development of moxEos3.2 and moxDendra2 9 had revealed that the cysteine positions were highly sensitive even to seemingly conservative small amino acid substitutions. Serine was never tolerated and an alanine or valine could produce dramatic differences in apparent brightness 3 , 5 , 18 .…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…It was not obvious a priori that the cysteines of mMaple3 could be mutated without disrupting the desirable properties of mMaple3. Similar efforts for EGFP family members often resulted in dark proteins and our previous efforts with the development of moxEos3.2 and moxDendra2 9 had revealed that the cysteine positions were highly sensitive even to seemingly conservative small amino acid substitutions. Serine was never tolerated and an alanine or valine could produce dramatic differences in apparent brightness 3 , 5 , 18 .…”
Section: Resultsmentioning
confidence: 84%
“…Consequently, these post-translational modifications and environmental effects can lead to FP misfolding, dark FPs, and mislocalization 3 6 . Recently, our groups successfully engineered FPs into “mox” (monomeric nonoxidizing or disulphide bonding) forms to improve their suitability for a wide variety of eukaryotic cellular compartments 5 , 9 . Here we turn our attention to develop an improved photoswitchable FP to optically highlight fusion proteins to study their fate and for single-molecule-based photoactivation localization microscopy PALM super-resolution imaging 10 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The labeled fusion proteins MTS:BDFP2.0 and NLS:BDFP1.1 can be coexpressed correctly in HeLa cells, and interference between the two protein markers can be greatly reduced because of a large gap between the two excitation lasers (Figure ). These results indicate that BDFP2.0 can be correctly folded in cells and the resulting chromophores are highly stable, which does not alter the localization, function, and behavior of a tagged fusion protein …”
Section: Resultsmentioning
confidence: 89%
“…The size‐exclusion chromatography results indicate that BDFP2.0 may have two aggregation states, that is, the majority is a dimeric state (75 kDa) and the minority is a monomeric state (45 kDa) in solution (Figure S3 B). To test this, we fused BDFP2.0 to the monomericity reporter CytERM, which expressed the reporter in HeLa cells and imaged cells for evidence of membrane accumulation by oligomeric proteins . The results of the CytERM assay also suggested that BDFP2.0 might exist as a dimer in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation